Fouskas V. – Dimoulas C. (2013), Greece, Financialization and the EU. The Political Economy of Debt and Destruction, Basingstoke: Palgrave Macmillan. - Κουραχάνης, Νίκος (Κοινωνική Πολιτική, 2017)
Μη Διαθέσιμη Περίληψη